Eveningness and Later Sleep Timing Are Associated with Greater Risk for Alcohol and Marijuana Use in Adolescence: Initial Findings from the National Consortium on Alcohol and Neurodevelopment in Adolescence Study. (29th May 2017) - Hasler, Brant P.; Franzen, Peter L.; de Zambotti, Massimiliano; Prouty, Devin; Brown, Sandra A.; Tapert, Susan F.; Pfefferbaum, Adolf; Pohl, Kilian M.; Sullivan, Edith V.; De Bellis, Michael D.; Nagel, Bonnie J.; Baker, Fiona C.; et al.
Abstract : Background: Abundant cross‐sectional evidence links eveningness (a preference for later sleep–wake timing) and increased alcohol and drug use among adolescents and young adults. However, longitudinal studies are needed to examine whether eveningness is a risk factor for subsequent alcohol and drug use, particularly during adolescence, which is marked by parallel peaks in eveningness and risk for the onset of alcohol use disorders. This study examined whether eveningness and other sleep characteristics were associated with concurrent or subsequent substance involvement in a longitudinal study of adolescents. Methods: Participants were 729 adolescents (368 females; age 12 to 21 years) in the National Consortium on Alcohol and Neurodevelopment in Adolescence study. Associations between the sleep variables (circadian preference, sleep quality, daytime sleepiness, sleep timing, and sleep duration) and 3 categorical substance variables (at‐risk alcohol use, alcohol bingeing, and past‐year marijuana use [y/n]) were examined using ordinal and logistic regression with baseline age, sex, race, ethnicity, socioeconomic status, and psychiatric problems as covariates. Results: At baseline, greater eveningness was associated with greater at‐risk alcohol use, greater bingeing, and past‐year use of marijuana. Later weekday and weekend bedtimes, but not weekday or weekend sleep duration, showed similar associations across the 3 substance outcomes at baseline. Greater baseline eveningness was also prospectively associated with greater bingeing and past‐year use of marijuana at the 1‐year follow‐up, after covarying for baseline bingeing and marijuana use. Later baseline weekday and weekend bedtimes, and shorter baseline weekday sleep duration, were similarly associated with greater bingeing and past‐year use of marijuana at the 1‐year follow‐up after covarying for baseline values. Conclusions: Findings suggest that eveningness and sleep timing may be under recognized risk factors and future areas of intervention for adolescent involvement in alcohol and marijuana that should be considered along with other previously identified sleep factors such as insomnia and insufficient sleep. Abstract : Here, we examined whether sleep timing and other sleep characteristics were associated with concurrent or subsequent substance involvement in 729 adolescents from the National Consortium on Adolescent Neurodevelopment and Alcohol study. After accounting for covariates, greater eveningness (later preferred sleep timing; left panel) and later bedtimes (right panel) were associated with more extreme binge alcohol use both at baseline and at the 1‐year follow‐up. Eveningness and sleep timing may be under‐recognized risk factors and potential intervention targets for adolescent alcohol misuse.